Skin microbiota variation in Indian families - Potbhare, Renuka; RaviKumar, Ameeta; Munukka, Eveliina; Lahti, Leo; Ashma, Richa (PeerJ Inc., 2025)
Background: In India, joint families often encompass members spanning multiple generations cohabiting in the same household, thereby sharing the same ethnicity, genetics, dietary habits, lifestyles, and other living conditions. Such an extended family provides a unique opportunity to evaluate the effect of genetics and other confounding factors like geographical location, diet and age on the skin microbiota within and between families across three generations.
Methods: The present study involved seventy-two individuals from fifteen families from two geographical regions of Maharashtra, India. The 16S rRNA sequencing of V3-V4 regions was performed and the generated taxonomic profiles were used for downstream analysis.
Results: Our study highlights a significant difference in community composition (beta diversity) between families (PERMANOVA; p = 0.001) and geographical locations (p = 0.001). We observed geographical location-wise differences in the relative abundances Staphylococcus in the families from Pune (Wilcoxon test, p = 0.007), and Bacillus in the Ahmednagar families (Wilcoxon test, p = 0.004). When within and between-family comparisons of skin microbiota composition were carried out between different generations (G1-G2, G2-G3, and G1-G3); we observed skin microbiota tended to be more similar within than between families but this difference was not significant.
Conclusion: This study underscores the diversity and commonalities in skin microbiota composition within and between families. Our result suggests that geographical location is significantly associated with the genus composition of skin microbiota, which is quantitatively unique for a family and likely explained by co-habitation.